Frontispiece: Synthesis and Optical Properties of Phenanthroline‐Derived Schiff Base‐Like Dinuclear RuII–NiII Complexes. Issue 20 (10th April 2018) - Kurz, Hannah; Lochenie, Charles; Wagner, Kristina G.; Schneider, Sandra; Karg, Matthias; Weber, Birgit
Abstract : The picture shows a nickel(II) complex with a phosphorescent ruthenium(II)‐based metalloligand. The photoluminescence properties of the dinuclear complex can be controlled through variation of the spin state at the nickel(II) center via coordination‐induced spin state switch (CISSS). For the diamagnetic square planar nickel(II) center phosphorescence is observed while coordination of additional ligands results in a paramagnetic spin state and photoluminescence quenching. For more information, see the Full Paper by M. Karg, B. Weber, et al. onpage 5100 ff.